A mesoionic nitrogen-donor ligand: structure, iridium coordination, and catalytic effects. Issue 3 (14th December 2017) - Navarro, Miquel; Li, Mo; Bernhard, Stefan; Albrecht, Martin
Abstract : A first example of a mesoionic ligand with a nitrogen coordination site was prepared by a simple and robust synthesis and is shown to have excellent properties for promoting iridium-catalyzed water oxidation. Abstract : A mesoinic pyridylideneamide ligand (PYA) was synthetized and fully characterized and coordinated to an iridium(iii ) center. This ligand represents the first example of a mesoionic N-donor ligand. Structural and spectroscopic analysis revealed unique properties which were exploited in chemically driven water oxidation catalysis.